THE TOTAL MELANINS CONTENT OF BASIDIOMYCETES ORDERS POLYPORALES AND AGARICALES - А. К. Велигодська; О. В. Федотов (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2013)
The aim of the study was to investigate the total content of melanin in carpophorus, mycelia and culture filtrate species of Basidiomycetes. Methods. Extraction of melanin mycological material carried by its alkali hydrolysis 2 N NaOH solution in the ratio of 1:10, followed by precipitation with concentrated HCl. The precipitate after the addition of hydrochloric acid dissolved in 5 ml of 2 N solution of NaOH. The total pigment content was determined by spectrophotometric method and were calculated using a calibration curve (by pyrocatechol). The melanin content in the culture filtrate was determined by the direct colorimetry CF. Results. The total melanin content in fruiting bodies of 50 species of Basidiomycetes, 27 of which are belonging to order Polyporales and 23 to order Agaricales was investigated. The comparative analysis on the basis of the obtained data showed the highest total melanin content in Ganoderma applanatum, Fistulina hepatica and Laetiporus sulfureus сarpophorus. Dynamics of growth and carotenoid synthesis in mycelium and cultural filtrate of 30 strains of 10 basidiomycetes species isolated in mycelial culture was studied on glucosepeptone medium. Conclusion. Selected strains of Fomes fomentarius and Lentinus edodes are promising for further studies to optimize the culture conditions for mycelial melanin origin.